If x + y = 4, xy = 2, y + z = 5, yz = 3, z + x = 6 and zx = 4, then find the value of $x^3 + y^3 +z^3 - 3xy.$ |
150.75 152.75 151.75 153.75 |
153.75 |
If x + y = 4, xy = 2, y + z = 5, yz = 3, z + x = 6 and zx = 4 We know that, x3 + y3 + z3 - 3xyz = (x + y + z) × (x2 + y2 + z2 – xy – yz – zx) (x + y)2 = x2 + y2 + 2xy x + y = 4, y + z = 5, z + x = 6 x + y + z = 7.5 xy + yz + zx = 2 + 3 + 4 = 9 Now, (x + y)2 = x2 + y2 + 2xy x2 + y2 = 16 – 4 = 12 Because..(2xy = 4) (y + z)2 = y2 + z2 + 2yz y2 + z2 = 25 – 6 = 19 Because...(2yz = 6) (x + z)2 = x2 + z2 + 2xz x2 + z2 = 36 – 8 = 28 Because...(2zx = 8) So, 2x2 + 2y2 + 2z2 = 12 + 19 + 28 = 59 x2 + y2 + z2 = 29.5 Now, x3 + y3 + z3 - 3xyz = (x + y + z) × (x2 + y2 + z2 – xy – yz – zx) = (7.5) × (29.5 – 9) = 7.5 × 20.5 = 153.75 |